POTENSI Ca, P, Mg, DAN Zn PADA BERBAGAI BAGIAN TANAMAN KIAMBANG (Salvinia molesta) DI BENDUNGAN BATU TEGI KABUPATEN TANGGAMUS - Boby Sanjaya; Farida Fathul; Rudy Sutrisna (JURNAL ILMIAH PETERNAKAN TERPADU, 2013)
The increase of population in Indonesia has caused farmland increasingly narrow. In contrast, the more limited availability of green feed and causing feed prices continue to rise every year.  Therefore, alternative feed resources needed are cheap, readily available, abundant in nature and highly nutritious.  Expected to be sufficient alternative feed feed shortages due to narrowing of agricultural land and reduce production costs.  This study aims to determine the elemental content of Ca, P, Mg and Zn in plant parts Kiambang (Salvinia molesta).  This research was conducted at the Batu Tegi Dam Tanggamus Lampung regency and Animal Nutrition Laboratory Department of Dairy and Nutrition Faculty of Animal Science, Bogor Agricultural University.  This research used Completely Randomized Design 5 treatments with 2 replications. Treatment consists of young leaves, old leaves, old roots, young roots and whole plants Kiambang.  The data obtained in this study were analyzed on a variety of real level of 5% and 1% Test, BNT used as a means of comparison between treatments in the real level of 5%.  The results showed that.  (1) Kiambang contain elements Ca, P and Zn in the roots of the old site, while the largest element Mg on older leaves.  (2) Kiambang (Salvinia molesta) has potential as a source of essential minerals (Ca, Mg and Zn) for organic ruminants.   Keywords: Kiambang, mineral, Batu Tegi Dam